Pain in Long-Term Breast Cancer Survivors: Frequency, Severity, and Impact - Jensen, Mark P. (Pain Med, 2010)
OBJECTIVE: To better understand the severity and impact of pain in women who are breast cancer survivors. DESIGN: Cross-sectional survey. SETTING: Cancer wellness clinic. PATIENTS: Two hundred fifty-three women with a history of early-stage breast cancer who had completed therapy and were without evidence of disease. INTERVENTIONS: None. OUTCOME MEASURES: A survey that included questions about cancer history, pain, sleep problems, and physical and psychological functioning. RESULTS: About half of the participants (117 or 46%) reported some pain, although most rated its intensity as mild. Both average and worst pain ratings showed significant associations with physical functioning (rs, −0.48 and −0.43, respectively), severity of sleep problems (rs, 0.31 and 0.30), and psychological functioning (rs, −0.27 and −0.24). Age (with younger participants slightly more likely to report pain) and history of antiestrogen therapy showed nonsignificant trends to predict the presence of pain. CONCLUSIONS: The study findings provide new and important knowledge regarding the severity and impact of pain in female breast cancer survivors. The results indicate that clinicians should assess pain regularly in breast cancer survivors and treat this pain when indicated. The findings also support the need for research to determine whether improved pain management would result in improved quality of life for women with a history of breast cancer.